Ser boa professora na Escola Sacramentinas : histórias e memórias da educação em Amargosa/BA (1953-1990) - Silva, Ana Maria Barbosa da (2023)
The objective of this research is to investigate the construction of identity of women who studied at Ginásio Santa Bernadete and became teachers, in the city of Amargosa/BA, in the period between 1953 and 1990, based on the reference of valuing “being a good teacher”. This representation affects the Amargosa community as a whole. These teachers, former students of Escola das Sacramentinas, become references when it comes to quality teaching, due to the fact that upon graduating, they returned to the Gymnasium as teachers and taught in schools in the city. The discussions were held using as a cut-off the historical period that goes from 1953 to 1990. This time frame was established considering the period in which the institution began offering the Pedagogical Course to students in the city of Amargosa and region (1953) and the year and that the teacher who is the guiding force of this research was active in the job market (1990). The analysis is crossed by gender issues, considering that female education in Brazil is strongly marked by gender relations. The problematization is anchored in authors such as Louro (2014), Passos (1999) and other researchers on the topic of female education. Some concepts are fundamental, including memory and identity. Oral History constitutes the methodological approach, because from it we have the opportunity to listen and share memories of the interviewees, give meaning to the experiences lived, and also value the individual or collective human experience. In addition to the interviews, the dissertation is based on the analysis of documents found in the school archive and other primary sources.